2023
DOI: 10.3390/ma16041752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Walnut-Shell Additive on the Structure and Characteristics of Concrete

Abstract: The partial replacement of the mineral components of concrete with natural renewable analogues in full possession of the performance characteristics of the final material, allows not only the concrete-production process to be made more environmentally friendly and inexpensive, but also to solve an important task for the agricultural industry, which is that associated with waste disposal. The scientific novelty of the work is in the obtaining of new concrete compositions by the partial replacement of coarse agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The designs of the concrete mixture of the control composition and the mixtures with different CS contents are compiled in Table 6. The choice of the proportions of the concrete mixtures (water-cement ratio, percentage of CS and other parameters) was based on the concrete compositions already selected by us in previous works [14,15] and the works of other authors [33,34,46], with their adjustment related to the properties of the components used [51].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The designs of the concrete mixture of the control composition and the mixtures with different CS contents are compiled in Table 6. The choice of the proportions of the concrete mixtures (water-cement ratio, percentage of CS and other parameters) was based on the concrete compositions already selected by us in previous works [14,15] and the works of other authors [33,34,46], with their adjustment related to the properties of the components used [51].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, materials scientists are faced with the question of studying the fundamental nature of the processes and physicochemical processes that take place during the formation of the structure and properties of building materials using plant waste. Of particular difficulty and at the same level of interest is the determination of the most rational quantities and the degree of compatibility and effectiveness of the combination of plant wastes in the body of mineral components of other materials, including concrete [ 5 , 13 , 14 , 15 ]. Recently, the question of the inconsistency of the concept of sustainable development with this approach of using natural mineral resources, for example river sand and crushed stone, for the needs of the construction industry has been increasingly raised [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be incinerated or used as a raw material in different industrial processes, such as flours and bases for soaps [ 16 , 21 ]. More recently, Beskopylny et al [ 22 ] used walnut shells as an additive in the production of concrete. In another study, Sowińska-Baranowska et al [ 23 ] showed the potential application of walnut shells as biofillers for natural rubber composites.…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that when coarse and fine aggregates were replaced with walnut shells separately, the dry density and mechanical properties of the mortar decreased except for water absorption, and the overall performance was best when coarse and fine aggregates were replaced together. Alexey N. Beskopylny et al [23] utilized walnut shells as equal volume replacements for coarse aggregates in concrete (5% to 30%), and the density, compressive, flexural, and tensile properties of the concrete were studied. The test results showed that at 5% replacement of walnut shells, the strength properties of the concrete increased by 3.5%, the strength-to-density ratio reached its maximum value, a 10% reduction in crushed stone consumption, and a 6% reduction in concrete mass.…”
Section: Introductionmentioning
confidence: 99%